A new instantaneous performance parameter for alpine skiing and individual sports - Gilgien, M.; Haugen, P.; Reid, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: To help gain insight into the intricacies of athlete performance in alpine ski racing, several measures of instantaneous performance have been proposed (Federolf, 2012; Supej, 2010). Since alpine ski races are held on inclined slopes, these instantaneous performance measures are usually expressed as functions of the instantaneous vertical altitude drop of the skier. (Supej, 2010) employed change in mechanical energy per altitude drop as a performance measure while (Federolf, 2012) employed difference in path length and speed per altitude drop as a performance measure. These measures are valid as long as the slope includes a vertical drop, but fail when the terrain is flat or uphill. Therefore, this study presents a new instantaneous performance measure that is independent of the slope inclination and therefore more applicable in the analysis of entire courses. Methods: Athlete center of mass trajectories were captured by either video-based photogrammetry (Reid, 2010) or GNSS (Gilgien, 2015). Speed and path length were computed for each position along the trajectories (Reid, 2010). For each analyzed course, an average trajectory was calculated from the start to finish line based on all skier trajectories. A virtual plane was spanned normal to the average trajectory every 30 cm and was intersected with each of the single trajectories (Supej et al., 2011). At each intersection point, values for time, speed, path length and forces were interpolated and stored as a function of the distance from the start to the virtual plane in question. Results: Instantaneous performance was expressed as time differences to the leader in the finish as a function of distance from start. To explain the differences in performance time, speed and path length were expressed as differences to the speed and path length values of the leader as a function of the distance from start. Forces were used in combination with time synchronized video of the skiing to explain the reasons for speed differences that occured. Discussion: Since GPS technology is applied in alpine skiing entire runs are tracked instead of some turns as it was common with video based photogrammetry. Hence, a larger range of terrain inclinations is included in the data sets, also flat and uphill terrain (Gilgien, 2015). The new performance parameter facilitates instantaneous performance analysis in any type of terrain and skiing discipline. The measures applies also to other individual sports like motorsport or cycling.